Facilitating teachers' reuse of mobile assisted language learning resources using educational metadata - Zervas, P.; Sampson, Demetrios (Institute of Electrical and Electronics Engineers, 2014)
Mobile assisted language learning (MALL) and open access repositories for language learning resources are both topics that have attracted the interest of researchers and practitioners in technology enhanced learning (TeL). Yet, there is limited experimental evidence about possible factors that can influence and potentially enhance reuse of MALL resources stored in open access repositories. In this paper the Mobile2Learn Framework is proposed, which aims at supporting sharing and reuse of MALL resources within the context of MALL courses development. Moreover, a quantitative analysis of the reuse of MALL resources developed with the proposed Mobile2Learn Framework is conducted. The results of this analysis provided with evidence that completeness of metadata fields related with educational objectives based on Common European Framework of Reference for Languages (CEFR) can strongly influence reuse taking place among Mobile2Learn Framework users. © 2013 IEEE.